2012
DOI: 10.1093/jpepsy/jss044
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Maternal Mental Health: A Prospective Study of Mothers of Infants With Congenital Heart Defects From Pregnancy to 36 Months Postpartum

Abstract: Mothers of infants with severe CHD are at risk of compromised mental health from delivery to 36 months postpartum. Strain due to CHD-related interventions is identified as a possible partial mediator of the distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
3
35
0
1
Order By: Relevance
“…This is in line with previous studies showing higher rates of anxiety, depression or post-traumatic stress disorder in mothers of children with CHD (Lawoko & Soares, 2002. As previous studies with samples from the MoBa have shown, mothers of children with severe CHD are most probably at the highest risk (Solberg et al 2011(Solberg et al , 2012. This suggests that a considerable share of mothers may need psychological support after giving birth to a child with CHD.…”
Section: Mental Health Of Children With Chd and Their Motherssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with previous studies showing higher rates of anxiety, depression or post-traumatic stress disorder in mothers of children with CHD (Lawoko & Soares, 2002. As previous studies with samples from the MoBa have shown, mothers of children with severe CHD are most probably at the highest risk (Solberg et al 2011(Solberg et al , 2012. This suggests that a considerable share of mothers may need psychological support after giving birth to a child with CHD.…”
Section: Mental Health Of Children With Chd and Their Motherssupporting
confidence: 91%
“…As M and C are the background factors for mental health, the effects of M and C work indirectly through the third paths of mutual influences. Given that mothers of children with CHD and mothers of children in the normal cohort did not differ in distress before birth (Solberg et al 2012), we assume that the child's CHD causes distress in both mothers and children after birth. Such an additional cause creates additional variance.…”
Section: Structural Equation Modelingmentioning
confidence: 99%
“…), while a study on families with a child with Down Syndrome found that the highest proportion of divorce took place in these families in the first two years following birth (Solberg et al . ). However, these studies have limitations in terms of generalizability and transferability of their conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers of infants with congenital heart disease experience short and long-term depression and anxiety 32,33,34 . This maternal depression may interfere with normal early bonding, and bonding problems may persist to 1 year 15 .…”
Section: Discussionmentioning
confidence: 99%